CHD4 in the DNA-damage response and cell cycle progression: not so NuRDy now. (23rd May 2013) - O'Shaughnessy, Aoife; Hendrich, Brian
Abstract : The CHD4 (chromodomain-helicase-DNA-binding 4) (or Mi-2β) protein is a founding component of the NuRD (nucleosome remodelling and deacetylation) complex. NuRD has long been known to function in transcriptional regulation, and is conserved throughout the animal and plant kingdoms. In recent years, evidence has steadily accumulated indicating that CHD4 can both function outside of the NuRD complex and also play important roles in cellular processes other than transcriptional regulation. A number of loss-of-function studies have identified important roles for CHD4 in the DNA-damage response and in cell cycle progression through S-phase and into G2 . Furthermore, as part of NuRD, it participates in regulating acetylation levels of p53, thereby indirectly regulating the G1 /S cell cycle checkpoint. Although CHD4 has a somewhat complicated relationship with the cell cycle, recent evidence indicates that CHD4 may exert some tumour-suppressor functions in human carcinogenesis. CHD4 is a defining member of the NuRD complex, but evidence is accumulating that CHD4 also plays important NuRD-independent roles in the DNA-damage response and cell cycle progression, as well as in transcriptional regulation.